Redescription of Leptoconops (Leptoconops) brasiliensis (Lutz) and Leptoconops (Megaconops) floridensis Wirth (Diptera: Ceratopogonidae) with its first Brazilian record - Santarém, Maria Clara Alves; Cremer, Marta Jussara; Vieira, Jenyffer Vierheller; Lemos, Giulia Gaglianone; Pecor, David B.; Felippe-Bauer, Maria Luiza (Zootaxa, 2023)
The Leptoconops Skuse genus includes many pestiferous biting midges found in coastal areas. Only two species were previously found in Brazil and some species have ancient descriptions lacking updated taxonomic features. Herein, we redescribe Leptoconops (Leptoconops) brasiliensis Lutz and L. (Megaconops) floridensis Wirth based on female type specimens and additional material from Goiás and Santa Catarina, Brazil. The first Brazilian record of L. (M.) floridensis is reported.